Análise comparativa entre o planejamento estratégico do Estado do Rio de Janeiro e o da região Midtjylland, na Dinamarca - Jesus, Igor Rosa Dias de (2009)
This paper presents a comparative analysis of the government strategic planning of government for two apparently distant realities: State of Rio de Janeiro, Brazil, and Region Midtjylland (Central Denmark Region), Denmark. The objective of this study is to compare both approaches and provide academic and methodological enrichment about the management of government strategic plans in two different institutional contexts, namely, Rio de Janeiro and Midtjylland and, to a greater extent, Brazil and Denmark. The comparison is made in nine different ways, namely: regional power, methodology, partnerships, time horizon, politician issues, popular participation, forms of monitoring, external variables, regional image and regional integration. Furthermore, this work also aims to understand how the institutional tasks work as a limitation for using preconceived models of strategic planning on public management. At last, this work, for its content and approach, aims to be an element of rapprochement between Engineering, especially Production Engineering, and Public Management.